Analisis Simpangan Pada Portal Terbuka dan Portal Tertutup Pada Bangunan Bertingkat Beton Bertulang - Desnalia, Desnalia lia; Wibowo, Leonardus Setia Budi; Purwanto, Didik; Ray, Norman (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
In designing structures such as portals, planning generally does not take into account filler components such as bricks as structural components, only considered non-structural components / flat sharing loads. In fact, the infill wall is composed of bricks with mortars which have a certain strength and rigidity. As a result, when an earthquake occurs, the most damage is to buildings with brick infill walls In this study, two types of high-level building floors were made, namely 5 floors and 10 floors with 2 structural models of each level, namely the open and closed portal structure models that function as hotels using soft soil types in the Padang area, so the total structure model 2 structural models will be analyzed. The thickness of the wall is assumed to be an arrangement of half-brick walls with three barriers and four barriers. In the analysis of the brick wall structure is modeled as a diagonal compressed bracing equivalent to a brick wall (full brick) and then compared to a brick wall which is considered a flat sharing dead load (open portal). To analyze the behavior of this multi-story building structure, a Non-Linear (Pushover) static analysis will be carried out with the SAP 2000 assistance program. The results of the study showed the influence of strength and stiffness of the brick wall for the 5-way portal x was obtained by 71%, for the Y direction by 65%, while the 10-floor portal for x direction obtained the value of the brick wall stiffness by 58%, Y direction by 48%, and for portal 15 floors obtained strength and stiffness value of X direction by 52%, and for Y direction by 41%. The results of the study also showed that the structure of a closed portal with a brick wall has a better structural behavior compared to an open frame portal structure, this is indicated in the deviation value, a closed portal structure has a smaller value than an open portal structure. From the comparison of closed portal structures with brick walls, it can be concluded that the value of the rigidity of a structure is influenced by the span length and thickness of the brick wall. The bigger and thicker the dimensions of the brick wall, the greater the strength and stiffness values affect a reinforced concrete structure. This can be seen in the results of the ATC-40 pushover curve value, the value of the X direction brick wall with a span length of 5 m is greater than the value of the Y direction brick wall with a span length of 4 m.